Aplicação da reação de Pictet-Spengler na síntese de alcaloides fenil tetrahidroisoquinolínicos inéditos - Cordeiro, Manuela Barbosa (2012)
The number of alkaloids containing the 1-substituted tetrahydroisoquinoline skeleton is extensive and impressive versatility of this pharmacological class arouses interest in experimental pharmacologists. Applying the consecrated Pictet-Spengler reaction of four phenyltetrahydroisoquinoline alkaloids was obtained, three of which are unpublished. Two of them obtained with excellent yield (93.45%) in one step. Starting from allylbenzene that initially passed through an isomerization followed by oxidation by applying the Limieux-Johnson reaction were obtained from two other alkaloids with an overall yield of 50%. In experimental models of acute inflammation, the 1-(3-methoxy-4-hydroxyphenyl)-7-methoxy-1,2,3,4,tetrahydroisoquinoline (MTHP) significantly reduced (p <0.05) cell migration into the abdominal cavity of mice and the release of pro-inflammatory mediators (TNF-α, IL-1 and IL-6) in a dose one hundred thirty-eight times lower dosage than the dose of aspirin administered (200 mg/Kg).The MTHP causes hypotension in non-anesthetized normotensive rats, which can be attributed to the participation of endothelium-derived factors, including NO and metabolites COX. These data suggest that MTHP has anti-inflammatory and hypotensive effect related to different mechanisms, and further studies are needed to explore its potential.